2019
DOI: 10.1111/hir.12273
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐requisites, barriers and advantages of clinical informationist participation in grand round: a qualitative study

Abstract: Background: Clinical specialists require access to the most recent and up to date professional information. However, barriers such as insufficient time and lack of necessary information retrieval skills necessitate the presence of clinical informationist (CI) in medical teams.Objectives: This study sought to determine the pre-requisite for CI participation in the grand round. Methods: This was a qualitative study carried out using content analysis approach. Study involved all fellowship students and attending … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…In this issue, Ali and Gatiti (2020) share first‐hand experiences of the role of university librarians in raising awareness through public health education of COVID‐19, providing support to medical staff and researchers, and providing ongoing, traditional services to regular library patrons, while Ayatollahi & Zeraatkar, (2020) consider the factors influencing effective knowledge management processes in healthcare organisations. In less pressing times, Purnell (2020) presents the findings from her training needs analysis of the best ways of supporting health professionals undertaking research, Naeem and Bhatti (2020) considers measures of self‐efficacy among doctors in conducting online searches, and Zare‐Farashbandi et al (2020) explore the advantages, barriers and pre‐requisites of involving a clinical informationist in grand rounds. Lots of food for thought.…”
Section: In This Issue…mentioning
confidence: 99%
“…In this issue, Ali and Gatiti (2020) share first‐hand experiences of the role of university librarians in raising awareness through public health education of COVID‐19, providing support to medical staff and researchers, and providing ongoing, traditional services to regular library patrons, while Ayatollahi & Zeraatkar, (2020) consider the factors influencing effective knowledge management processes in healthcare organisations. In less pressing times, Purnell (2020) presents the findings from her training needs analysis of the best ways of supporting health professionals undertaking research, Naeem and Bhatti (2020) considers measures of self‐efficacy among doctors in conducting online searches, and Zare‐Farashbandi et al (2020) explore the advantages, barriers and pre‐requisites of involving a clinical informationist in grand rounds. Lots of food for thought.…”
Section: In This Issue…mentioning
confidence: 99%
“…The use of strong evidence reduces medical errors and ensures the quality of patient care [1]. However, factors such as lack of time and insufficient information-seeking skills prevent access to information [2,3]. Because of these barriers, many clinicians and physicians prefer to get needed information from convenient and easy sources, which may not be accurate [4].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have described the benefits of CI services and their performance. For instance, Zare-Farashbandi et al considered that the benefits of using CI services for clinical teams included providing necessary information, saving time, reducing costs for health care systems, facilitating publication of treatment results for rare cases, and teaching computer and information retrieval skills [3]. Other studies demonstrated that CIs can improve the information-seeking behavior of clinical professionals and medical students [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are some gaps in research about operational studies on CI, especially in Persian. [ 7 ] Since 2014, the CI research unit has been founded at Isfahan University of Medical Sciences to develop many projects focusing on the CI roles for the first time in Iran by Dr. Rahimi and Dr. Adibi. For example, their studies highlighted the CI educational skills needed in clinical teams that can be classified into three main types: general skills, informatics skills, and EBM skills.…”
mentioning
confidence: 99%